General and Specific Culture Learning in EFL Textbooks Aimed at Adult Learners in Spain - Rodríguez, Antonio R. Raigón; Espinar, Ángela Mª Larrea (Studia Anglica Posnaniensia, 2015)
Since language teaching in modern-day society is closely linked to cultural instruction, this study employs the model of a cultural learning analysis based on the earlier work of Paige and Lee. Using this model, the authors analysed the cultural content of six B1 and B2-level textbooks for teaching English to adults in Spain, and carried out a comparative study of the results, contrasting the two levels. Findings show that the subjective aspects of culture receive less coverage in textbooks, despite being fundamental to an understanding of the values of a society. Regarding the comparison between B1 and B2 levels, the data indicate that the number of big “C” Culture occurrences is similar for both levels, although there are differences in other cultural aspects. So, for example, culture in general is dealt with more at the B1 level, whereas small “c” culture is dealt with more at the B2 level.